2019
DOI: 10.1128/jvi.01092-19
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Based Protein Profiling Identifies ATG4B as a Key Host Factor for Enterovirus 71 Proliferation

Abstract: Virus-encoded proteases play diverse roles in the efficient replication of enterovirus 71 (EV71), which is the causative agent of human hand, foot, and mouth disease (HFMD). However, it is unclear how host proteases affect viral proliferation. Here, we designed activity-based probes (ABPs) based on an inhibitor of the main EV71 protease (3Cpro), which is responsible for the hydrolysis of the EV71 polyprotein, and successfully identified host candidates that bind to the ABPs. Among the candidates, the host cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…LAP, LANDO, and LC3/GABARAP-ylation are, to some degree, regulated by the ATG4 family of proteins, and thus the development of ATG4B inhibitors may impact on these processes in addition to the effects on canonical autophagy. Recently, it has been shown that ATG4B proteolytic activity is also essential for replication of enterovirus 71 and can process viral polyprotein, possibly indicating that other cellular targets for this protease exist [21].…”
Section: Introductionmentioning
confidence: 99%
“…LAP, LANDO, and LC3/GABARAP-ylation are, to some degree, regulated by the ATG4 family of proteins, and thus the development of ATG4B inhibitors may impact on these processes in addition to the effects on canonical autophagy. Recently, it has been shown that ATG4B proteolytic activity is also essential for replication of enterovirus 71 and can process viral polyprotein, possibly indicating that other cellular targets for this protease exist [21].…”
Section: Introductionmentioning
confidence: 99%
“…Enterovirus 71 protease (EV71) 3C pro is primarily responsible for the hydrolysis of EV71 polyprotein, which is the dominant etiological factor of human hand, foot, and mouth disease (HFMD). Sun et al reported that ATG4B could hydrolyze the substrate of EV71 3C pro and confirmed its indispensable role in viral proliferation through genetic disruption of ATG4B in vivo 142 …”
Section: Atg4 and Diseasesmentioning
confidence: 91%
“…However, several positive-sense, single-stranded RNA viruses (including Dengue virus and hepatitis C virus (HCV)), DNA viruses (such as Varicella-Zoster virus), and even bacteria (Helicobacter pylori or Mycobacterium marinum, for instance) have been demonstrated to activate autophagy to promote their replication/growth cycle at different stages [22][23][24][25]. Following Huang et al 's report that the induction of autophagy in vitro and the formation of autophagosome-like vesicles in vivo after EVA71 infection benefits EVA71 replication [26], increasingly more studies have shown the hijacking of autophagy by EVA71 [10,11,13]. However, one study implied that increased autophagy levels contribute to the inhibition of EVA71 replication [27].…”
Section: The Interplay Between Autophagy and Eva71 Replicationmentioning
confidence: 99%
“…For early events, the key component of the autophagy machinery autophagy related 4B cysteine peptidase (ATG4B) contributes to the maturation of early viral protein. ATG4B, a cysteine protease that cleaves pro-LC3 isoforms to form LC3-I, may function like EVA71 3C protein to hydrolyze the single polyprotein encoded by the EVA71 genome to generate early viral proteins to undergo the subsequent viral replication process [ 11 , 52 ]. The silencing of ATG4B expression attenuates EVA71 RNA levels and VP1 expression levels in EVA71-infected RD, HEK293T, HeLa, and Vero cells [ 11 ].…”
Section: The Interplay Between Autophagy and Eva71 Replicationmentioning
confidence: 99%
See 1 more Smart Citation